Правовідносини органів і установ виконання покарань з державними органами та недержавними інституціями - Яцишин, Михайло Михайлович; Yatsyshyn, M. (Львівський національний університет імені І. Франка, 2009)
У статті з позицій теорії держави і права, конституційного та інших галузей права розглянуто основні положення чинного законодавства щодо правовідносин органів і установ виконання покарань з державними та недержавними інституціями, розкрито організаційно-правові та управлінські засади цього багатоаспектного процесу. The article is devoted to the current laws provisions concerning legal relations of the enforcement of sentences bodies and institutions with state bodies and non-governmental organizations from the standpoint of the theory of the state and law, constitutional law etc. Organizational and legal as well as administrative principles of this many-sided process are clarified.
Legal relations of the enforcement of sentences bodies and institutions with state bodies and nongovernmental organizations
Keywords: правовідносини; державні органи; недержавні інституції; установи виконання покарань; legal relations; state bodies; non-governmental organizations; enforcement of sentences bodies